Improved ionic-liquid-functionalized macroporous supports able to purify nucleic acids in one step. (September 2020) - Neves, M.C.; Pereira, P.; Pedro, A.Q.; Martins, J.C.; Trindade, T.; Queiroz, J.A.; Freire, M.G.; Sousa, F.
Abstract: Nucleic acids are relevant biopolymers in therapy and diagnosis, for which their purity and biological activity are of crucial relevance. However, these features are difficult to achieve by cost-effective methods. Herein, we report the functionalization of a macroporous chromatographic support functionalized with an ionic liquid (IL) with remarkable performance to purify nucleic acids. An initial screening with distinct IL chemical structures supported in silica was carried out, allowing to identify the IL 1-methyl-3-propylimidazolium chloride as the most promising ligand. A chromatographic macroporous matrix able to be used in preparative liquid chromatography was then functionalized and binding/elution studies were performed. The IL 1-methyl-3-propylimidazolium chloride acts as a multimodal ligand with a remarkable dynamic binding capacity. This macroporous support allows the (one-step) purification of nucleic acids, namely small RNAs, ribosomal RNA, and genomic DNA, from a bacterial lysate, and can be regenerated and reused without compromising its separation performance. Graphical abstract: Image 1 Highlights: A macroporous matrix was functionalized with ionic liquids (IL) acting as chromatographic ligands. A one-step nucleic acids purification is achieved using the IL-functionalized matrices. Distinct classes of bacterial nucleic acids can be purified with the new macroporous matrix. The IL acts as a multimodal ligand and exhibits a remarkable binding capacity. The support can be regenerated and reused without compromising its separation performance.